THE DIAGNOSTIC ACCURACY OF ULTRASONOGRAPHY FOR THE DIAGNOSIS OF RIB FRACTURES IN PATIENTS PRESENTING TO EMERGENCY DEPARTMENT WITH BLUNT CHEST TRAUMA - DENİZBAŞI ALTINOK, ARZU; AKOĞLU, HALDUN; BUĞDAYCI, ONUR; ONUR, ÖZGE ECMEL (ELSEVIER SCIENCE INC, 2021)
Background: Rib fractures are the most common complications of blunt chest trauma (BCT). Computed tomography (CT) is the modality of choice for BCT, but with several disadvantages. Ultrasonography (US) is an inexpensive, readily available, and relatively harmless imaging alternative. However, a direct comparison of the sonographic evaluation of the rib as a whole with CT as a reference has not been performed to date. Objective: This study aimed to compare the diagnostic accuracy of US with CT for the detection of rib fractures in patients who presented to emergency department (ED) with BCT. Methods: We included a convenience sample of adult patients who presented to the ED with thoracic pain after BCT in the last 24 h in this prospective, observational, diagnostic accuracy study. The diagnostic utility of US performed by an emergency physician was compared with thorax CT. Results: The final study population included 145 patients. The diagnostic accuracy of US was 80% with a sensitivity of 91.2% and specificity of 72.7% for the detection of any rib fracture (positive likelihood ratio 3.4 and negative likelihood ratio 0.12). If we considered each rib separately, the sensitivity of US decreased to 76.7% and specificity increased to 82.7% (81.3% accuracy). Conclusions: A negative US of the site of the highest tenderness and neighboring ribs in a patient with BCT who presented to the ED with lateralizing pain decreases the possibility of a rib fracture significantly. However, a positive US performs poorly to specify the exact location and number of the fractured ribs. (C) 2020 Elsevier Inc. All rights reserved.
Keywords: ribs; emergency ultrasound; chest trauma; emergency medicine